2003
DOI: 10.1103/physrevb.67.024423
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of the spin-Peierls phase under pressure inCu1xMgxGeO<

Abstract: The effect of pressure is studied on highly Mg-doped CuGeO 3 , which at ambient pressure shows an antiferromagnetic transition but no spin-Peierls transition. The magnetic susceptibility under pressure was measured; the broad maximum around 60 K shifts to lower temperatures and the spin-Peierls ͑SP͒ transition reappears. The temperature-concentration phase diagram at various pressures was constructed and it was found that the SP phase region enlarges with pressure. These results mean that the enhancement of fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…The strength of the second-neighbor bonds can also be controlled by applying pressure to such systems. Masuda and co-workers 22 studied the effect of pressure on highly Mg-doped CuGeO 3 and found that the frustration is enhanced as the pressure is increased. Another example of material that exhibits nontrivial second-neighbor interaction is Cu 6 Ge 6 O 18Ϫx H 2 O studied by Hase and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…The strength of the second-neighbor bonds can also be controlled by applying pressure to such systems. Masuda and co-workers 22 studied the effect of pressure on highly Mg-doped CuGeO 3 and found that the frustration is enhanced as the pressure is increased. Another example of material that exhibits nontrivial second-neighbor interaction is Cu 6 Ge 6 O 18Ϫx H 2 O studied by Hase and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…12) This paper is concerned with the pressure-induced magnetic ordering in the spin gap system TlCuCl 3 .…”
Section: -7)mentioning
confidence: 99%
“…For example, after the observation of the SP transition in CuGeO 3 , 4 many works on this cuprate and the SP transition have been carried out. [5][6][7][8][9][10][11][12][13][14][15][16][17] This leads to further understanding of the SP system and quantum spin systems.…”
Section: Introductionmentioning
confidence: 97%
“…It is known that there exist nearest-neighbor and next-nearest-neighbor AF interactions in spin chains in the SP CuGeO 3 , 9,10 and there are reports that the value of ␣ in CuGeO 3 is larger than ␣ c . 10,15,17 However, since the SP transition occurs at low temperatures, the spin gap in CuGeO 3 is not caused solely by the competing AF interactions.…”
Section: Introductionmentioning
confidence: 99%